New Forests International Journal on the Biology, Biotechnology, and Management of Afforestation and Reforestation - Jacobs, Douglass F.; SpringerLink (Online service) (Dordrecht : Springer Netherlands : Imprint: Springer.)
New Forests publishes original papers on the fundamental and applied aspects of afforestation and reforestation for a broad international audience of scientists and practitioners. Journal articles concern the reproduction of trees and forests originating from seed, planted seedlings or coppice for the purposes of resource protection, timber production, and agro-forestry. Natural and artificial methods of regeneration and all stand structures from even-aged to uneven-aged are considered. Topics include general silviculture, plant physiology, genetics, biotechnology, ecology, economics, protection, and management of all stages in the process of afforestation and reforestation.
Keywords: Forestry; Forestry